Factors affecting separation and detection of bile acids by liquid chromatography coupled with mass spectrometry at negative mode - Yin, Shanshan (Anal Bioanal Chem, 2017)
Bile acids (BAs) are cholesterol metabolites with important biological functions. They undergo extensive host-gut microbial co-metabolisms during the enterohepatic circulation, creating a vast structural diversity and resulting in great challenges to separate and detect them. Based on the bioanalytical reports in the past decade, this work developed three chromatographic gradient methods to separate a total of 48 BA standards on BEH C18 column and HSS T3 column and accordingly unraveled the factors affecting the separation and detection of them by liquid chromatography coupled with mass spectrometry (LC-MS). It was presented that both the acidity and ammonium levels in mobile phases reduced the electrospray ionization (ESI) of BAs as anions of [M-H](-), especially for those unconjugated ones without 12-hydroxylation. It was also found that the retention of taurine-conjugates on BEH C18 column was sensitive to the strength of formic acid and ammonium in mobile phases. By using the volatile buffers with an equivalent ammonium level as mobile phases, we comprehensively demonstrated the effects of the elution pH value on the retention behaviors of BAs on both BEH C18 column and HSS T3 column. Based on the retention data acquired on C18 column, we presented the ionization constants (pKa) of various BAs with the widest coverage beyond previous reports. When we made attempts to establish the structure-retention relationships (SRR) of BAs, the lack of discriminative structural descriptors for BA stereoisomers emerged as the bottleneck problem. The methods and results presented in this work are especially useful for the development a reliable, sensitive, high-throughput and robust LC-MS bioanalytical protocols for the quantitative metabolomic studies.